Signature of curved QFT effects on the optical properties of deformed graphene. (6th March 2017) - Oliveira, O.; Chaves, A. J.; de Paula, W.; Frederico, T.
Abstract: The Dirac equation in curved space is used to study the optical transmittance of deformed graphene along a given direction. Our theoretical analysis of the available experimental data for the light transmittance suggests that the periodic ripple associated with the out-of-plane deformation observed in unstrained graphene explains the observations. Furthermore, the experimental uniaxial strained graphene for light transmittance shows two features, namely the modification of the law and the decrease of the amplitude of the oscillations with the polarization angle θ, which can be well accommodated within the theoretical analysis used here and provide further evidence of the validity of using QFT in curved space to understand two-dimensional materials.